PENGELOLAAN TINDAK LANJUT PENGADUAN MASYARAKAT PADA SIARAN â€œKABAR BUPATIKUâ€ DI KABUPATEN TEGAL - Etkisyan, Johan Arifin; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2018)
Follow-up is an activity undertaken in the framework of completing the management of public complaints. Community complaints management in Tegal District is conducted through the process of receiving, recording, reviewing, distributing, confirmation, clarification, research, inspection, reporting, follow-up, and archiving. The substance of the public complaint consists of: the substance of public complaint is supervised and the substance of public complaint that is not supervised.The research method used is qualitative research method with explorative research type. Data collection technique used is interview, documentation, and literature study. The informants in this research are LPPL Tegal Radio Slawi Ayu FM (Director & Host of "Kabar Bupatiku") and 13 Local Government Organization of Tegal Regency (Secretary of Goverment Service, Head of Division, Head of Sub Division and Section Head).The results of the research showed that the management of 37 community complaints that was not supervised on the 23 editions of the "Kabar Bupatiku" broadcast: 17 complaints have been followed up, 7 complaints are being followed, 4 complaints have not been followed up, and 9 complaints are not followed up. With this research, it is expected to be used as input material in the management of public complaints on the broadcast of " Kabar Bupatiku ".The recommendations that can be given to the Government of Tegal Regency is by making Standard Operating Procedures (SOP) management of complaints broadcast " Kabar Bupatiku " and by trying the attendance of the Regent to be able to escort complaints that are delivered on " Kabar Bupatiku" broadcastKeywords: Management, Follow-Up, No Supervision